EXPLORING VOCABULARY SIZE OF EFL STUDENTS: A CASE STUDY OF RURAL AREA - Akmal; Anggreni, Afrilia; Said, Mawardin M; Wahyudin (Journal of Language Testing and Assessment, 2025)
The aim of this research is to expose students’ vocabulary size of SMPN 1 Sindue Tobata Donggala. Mixed methods design was utilized which involved two classes. The sample of this research was the grade VIII students of SMPN 1 Sindue Tobata which consisted 42 students and the informants were 4 students who are at good and poor score. Test and interview were distributed to collect the data. Vocabulary Level Test (VLT) was given to identify the word level of the students and interview was conducted to identify the factors that make students are difficult to master vocabulary. Therefore, the results of this research present that 27% students are at 2000-word level, 28 % students are at 3000-word level, 19 % students are at 5000-word level and 26 % students are not categorized or below the 2000-word level. Lack of strategy and interest in learning English are indicated as the internal factor. In addition, lack of media, technology and environment support are indicated as external factor. Thus, the teacher can provide some solution to bridge and solve the student’s problem in improving their vocabulary size.